2022
DOI: 10.1038/s41598-022-06735-1
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic performance of symbiont-bearing foraminifera Heterostegina depressa affected by sunscreens

Abstract: Foraminifera are abundant unicellular organisms that play an important role in marine element cycles. A large benthic foraminifer obligatory bearing photosymbionts is Heterostegina depressa. We studied potential impacts of sunscreens available on the market on the activity of photosymbionts on H. depressa by means of pulse-amplitude modulated (PAM) fluorescence microscopy. We included four different sunscreens, with two of them sold as “conventional” and two more stated as “eco-friendly”. Further, the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Generally, the assemblages of living LBFs are highly dependent on physical parameters like habitat depth, light supply and water motion 7 . Observing LBFs activity is suitable to detect chemical contaminants in seawater 8 . Thus, regular monitoring of LBFs can be used as an important tool to characterize the health state of coral reefs.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the assemblages of living LBFs are highly dependent on physical parameters like habitat depth, light supply and water motion 7 . Observing LBFs activity is suitable to detect chemical contaminants in seawater 8 . Thus, regular monitoring of LBFs can be used as an important tool to characterize the health state of coral reefs.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that Zn is released into the environment as ZnO nanoparticles, which are harmful to a variety of organisms [ 33 , 47 ]. Lintner et al [ 34 ] tested the influence of sunscreens containing such nanoparticles on H. depressa and they noticed ZnO as a potential ingredient reduced the photosynthetic area of the symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of iron is associated with the regulation of algal communities in coastal upwelling regimes and assists in the development of diatom blooms [ 32 ]. Zinc (oxide) nanoparticles deriving from sunscreens released by human into the environment at global beaches are presumably considered harmful to a variety of marine microorganisms [ 33 , 34 ]. Highly increased (1044 x Zn enrichment) concentrations of Zn negatively affected the metabolism of foraminifera [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…We applied non-invasive PAM fluorescence imaging to assess possible effects of microplastic particles on foraminifera and particularly on the functionality of their photosymbionts. This PAM approach has been used in previous studies to measure effects of pollutants and environmental parameters like heavy metals, toxic substances, temperature and total alkalinity on foraminiferal symbiont activity [33][34][35] www.nature.com/scientificreports/ perspective, PAM imaging primarily indicates the condition of the photoactive symbionts, and thus provides indirect information on the host performance but important insight into holobiont systems biology. If addressing the whole organism (holobiont), complementary approaches are recommended.…”
Section: Microplastic Effects On Photosymbiont Activitymentioning
confidence: 99%